2022
DOI: 10.1108/qrj-01-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of using negotiated syllabus in EFL classes: exploring the undergraduate students' perceptions

Abstract: PurposeA couple of decades ago, the negotiated syllabus was introduced as an alternative to the predetermined syllabus. The review of the related studies shows the number of studies on the use of negotiated syllabus in English language teaching is scanty. The main purpose of the study was to explore the advantages/merits of employing negotiated syllabus in general English courses that undergraduate students take.Design/methodology/approachThe authors employed the phenomenology research method to deeply delve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It was revealed that the students' participation and learning responsibility were observed to be enhanced. Additionally, Pakdaman et al (2022b) found that negotiated curriculum improved learner autonomy and critical thinking in higher-education EFL classroom. Lastly, Peyvandi et al (2021) investigated the impact of the negotiated syllabus on Iranian students' autonomy.…”
Section: Negotiated Curriculum In Foreign Language Classroommentioning
confidence: 99%
See 3 more Smart Citations
“…It was revealed that the students' participation and learning responsibility were observed to be enhanced. Additionally, Pakdaman et al (2022b) found that negotiated curriculum improved learner autonomy and critical thinking in higher-education EFL classroom. Lastly, Peyvandi et al (2021) investigated the impact of the negotiated syllabus on Iranian students' autonomy.…”
Section: Negotiated Curriculum In Foreign Language Classroommentioning
confidence: 99%
“…They have found out that the negotiated syllabus affected learning and motivation positively. Likewise, Pakdaman et al (2022b) investigated the impact of negotiated syllabus on language anxiety and motivation in higher education EFL classes. The results showed that the negotiated syllabus affected foreign language anxiety negatively and motivation positively.…”
Section: Negotiated Curriculum In Foreign Language Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to bear in mind that L2 learners are not "empty receptacles but capable stakeholders" (Bhowmik & Chaudhuri, 2022, p. 1414, possessing individual and collective assets of education and experience (Covell et al, 2017;Kim & Guo, 2022). As a result, perhaps the time has come for the adoption of English language teaching methods that place learner contributions at the forefront in a collaborative "negotiated syllabus" where instructors and students engage in more equitable reciprocity (Breen & Littlejohn, 2000;Clarke, 1991;Pakdaman et al, 2022;Prior, 2020). This would ensure that the devised language pathway is in alignment with learner outcomes, needs, and future goals (Douglas et al, 2022;Tweedie & Kim, 2015;Walková & Bradford, 2022) with an "appropriate balance of language and subject knowledge" (Shi, 2018, p. 20).…”
Section: Conclusion and Further Recommendationsmentioning
confidence: 99%